Pengalihan Wakaf oleh Sarak Opat di Aceh Tengah Ditinjau Hukum Islam dan Hukum Adat - Hazar Kusmayanti (Al-Manahij: Jurnal Kajian Hukum Islam, 2021)
Waqf is one of the institutions of Islamic social institutions that contain socio-economic values that are expected to help to realize social welfare that benefits can be enjoyed together. However, there are many problems related to waqf land, one of which is the change in the designation of waqf land-based on adat meetings. The purpose of this thesis is to examine the legal position of waqf land that has changed its designation and implementation of waqf in Central Aceh District based on Islamic Law and Customary Law in terms of the Law. The research in this thesis uses the normative juridical approach The specification of the research conducted is analytical descriptive. Based on the results of this study, the legal status of waqf land that has been represented cannot be used if it is not in accordance with the waqf pledge, but there are exceptions to the waqf land that can be changed its designation and must follow the procedure for changes stipulated by Law Number 41 of 2004 Execution of existing land parcels in Central Aceh Regency, Islamic Law has been implemented correctly, but the state administration has not been implemented to the maximum.